Analisis Pengaruh Perilaku Konsumtif Dan Tingkat Pendapatan Terhadap Online Shopping Pada E-Commerce Shopee Dalam Perspektif Ekonomi Islam - Marwiyah, Siti Laelatul; Ainulyaqin, MH; Edy, Sarwo (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this study was to analyze the effect of consumptive behavior and income levels on student online shopping at Shopee e-commerce. This research uses quantitative methods. The total population in this study was 325 people. The sampling technique in this study was obtained using a purposive sampling method. Purposive sampling is a sampling technique with certain considerations. Based on purposive sampling, the respondents taken in this study were Active Students of FAI at Pelita Bangsa University who worked and had or often used Shopee e-commerce as a shopping medium, resulting in 80 samples by calculating the slovin formula. The data used in this study are primary data obtained by distributing questionnaires. Partial Least Square (PLS) with the help of the SmartPLS version 4.0 application is used as data analysis in this study through three stages of testing, namely: evaluation of the measurement model (outer model), evaluation of the structural model (inner model) and hypothesis testing. The results of the study show that consumptive behavior has a positive and significant effect on online shopping. Income level has a positive and significant effect on online shopping. Consumptive behavior and income levels simultaneously influence online shopping with an R-square value of 0.591 or 59.1% and an adjusted R-square of 0.581 or 58.1%.